Awareness of Intergroup Help Can Rehumanize the Out-Group. (July 2015) - Saguy, Tamar; Szekeres, Hanna; Nouri, Rikki; Goldenberg, Amit; Doron, Guy; Dovidio, John F.; Yunger, Chaim; Halperin, Eran
Dehumanizing the enemy is one of the most destructive elements of intergroup conflict. Past research demonstrated that awareness of harm that the in-group imposed on a specific out-group can increase out-group dehumanization as means of justifying the harm. In this research, we examined whether the opposite process would occur when people become aware of help given to an adversary. We reasoned that the need to justify a good deed toward a persistent enemy can result in more human-like out-group attributions. In two experiments, Israeli-Jews read about their group either helping Palestinians or not. In Study 1, awareness of help provided by the in-group to the out-group resulted in greater out-group humanization. In Study 2, we further established that when a third party helped the out-group, the rehumanization effect was not obtained, suggesting that the phenomenon is of specific intergroup nature. Theoretical and applied implications for conflict resolution are discussed.